Accessibility Concerns on COVID-19 Information Websites for Persons with Disability - Hanny Hafiar; Syauqy Lukman; Putri Limilia; Wahyu Caesarendra; Kholidil Amin (Ikatan Sarjana Komunikasi Indonesia, 2022)
Persons with disabilities are a vulnerable group when obtaining reliable information, particularly during the current Pandemic of COVID-19. This group needs accurate and dependable information related to the effort of prevention, treatment, and other information on the Pandemic. Each 34 provincial government of Indonesia has their own dedicated COVID-19 information websites providing such information to the public. This study attempt to find accessibility issues that would impact a person with disabilities on all 34 COVID-19 websites managed by each respective provincial government. This study uses aXe (https://www.deque.com), an online tool that measures the total accessibility issues, types of issues, and impacts on people with disabilities on a website. Most COVID-19 websites managed by the provincial government have shown many issues, indicating failure to comply with the web content accessibility guidelines. The biggest issue is insufficient color contrasts in elements and images and the absence of illustrative text, which are very important for a person with visual impairment. We also find that level of accessibility is not correlated with the number of visitors.